Myocardial content of selected elements in experimental anthracycline-induced cardiomyopathy in rabbits - Simůnek, Tomás; Sterba, Martin; Holecková, Magdaléna; Kaplanová, Jana; Klimtová, Ivona; Adamcová, Michaela; Gersl, Vladimír; Hrdina, Radomír (Biometals, 2005)
Cardiotoxicity represents the main drawback of clinical usefulness of anthracycline antineoplastic drugs. In this study, a content of selected elements (Ca, Mg, K, Se, Fe) in the post-mortem removed samples of the myocardial tissue was studied in three groups of rabbits: 1) control group (i.v. saline; n = 10); 2) daunorubicin-receiving animals (DAU; 3 mg/kg, i.v; n = 11); 3) animals receiving cardioprotective iron-chelating agent dexrazoxane (DEX; 60 mg/kg, i.p.; n = 5) prior to DAU. Drugs were administered once weekly for 10 weeks. 5-7 days after the last administration, cardiac left ventricular contractility (dP/dtmax) was significantly decreased in DAU-treated animals (745 +/- 69 versus 1245 +/- 86 kPa/s in the control group; P < 0.05), while in the DEX + DAU group it was insignificantly increased (1411 +/- 77 kPa/s). Of the myocardial elements' content studied, a significant increase in total Ca against control (16.2 +/- 2.4 versus 10.6 +/- 0.9 microg/g of dry tissue; P < 0.05) was determined in the DAU-group, which was accompanied with significant decreases in Mg and K. In the heart tissue of DEX-pretreated animals, no significant changes of elements' content were found as compared to controls, while the Ca content was in these animals significantly lower than in the DAU group (9.1 +/- 0.4 versus 16.2 +/- 2.4 microg/g; P < 0.05). Hence, in this study we show that systolic heart failure induced by chronic DAU administration is primarily accompanied by persistent calcium overload of cardiac tissue and the protective action of DEX is associated with the restoration of normal myocardial Ca content.
Keywords: Magnesium; razoxan; Animals; draslík; hořčík; Rabbits; selen; stopové prvky; Potassium; železo; protinádorová antibiotika; antracykliny; Trace Elements; kardiomyopatie; Anthracyclines; Antibiotics, Antineoplastic; vápník; Calcium; Male; modely nemocí na zvířatech; Iron; Selenium; Disease Models, Animal; Cardiomyopathies; králíci; zvířata; mužské pohlaví; Razoxane; Myocardium; myokard